An iodine effect in ambipolar organic field-effect transistors based on indigo derivatives1. Issue 33 (7th September 2015) - Pitayatanakul, Oratai; Iijima, Kodai; Ashizawa, Minoru; Kawamoto, Tadashi; Matsumoto, Hidetoshi; Mori, Takehiko
<x xml:space="preserve">Abstract</x> 5, 5′-Diiodoindigo exhibits excellent ambipolar transistor properties with hole/electron mobilities of μh/μe = 0.42/0.85 cm2 V−1 s−1.